Business in practice: driving enigma motors on the road to electrification - a journey of performance analysis and self-reflection - Aleem, Saima Tofique (2024)
Business in Practice encapsulates professional experiences derived from a simulation, particularly amidst the transition to electrification within the automotive industry, alongside personal growth during this period. Reflecting on Enigma Motors' dynamics, this exploration unveils the crucial role of each company area (Strategy, Human Resources, Finance, Innovation, Marketing, and Operations), challenges in diverse teamwork, and the influence of individual personalities on performance. It underscores the significance of effective leadership, emphasizing communication, adaptability, and resilience in navigating complex business scenarios. Through BiP, skills are honed, networks amplified, and unwavering confidence instilled for future challenges, marking a transformative journey in real-world business dynamics.